THE MARKHOTOM AL-QUR'AN TRADITION AMONG ELDERLY WOMEN AT MAJELIS TAKLIM MISBAHUS SUDUR, PIDOLI DOLOK, PANYABUNGAN DISTRICT - Syaripah Aini; Akmal Gunawan; Amiruddin . (Magister Ilmu Al-Qur'an dan Tafsir UINSU Medan, 2026)
This research is a Living Qur’an study on the Markhotom tradition practiced by the Majelis Taklim in Pidoli Dolok, Panyabungan District, Mandailing Natal Regency. Markhotom is a local term referring to the activity of reciting the Qur’an in turns or collectively, usually carried out to strengthen Islamic brotherhood and deepen spirituality, particularly among elderly women. The Markhotom tradition of Majelis Taklim Misbahus Sudur in Pidoli Dolok is a practice rooted in the local wisdom of the Pidoli community. Every Friday afternoon, members of the Majelis Taklim mostly elderly women gather to carry out the Markhotom activity. This activity is held once a week and has become a highly anticipated spiritual routine for its members. This study is a field research project with a descriptive qualitative approach, employing the Living Qur’an method. The data sources in this research were collected through interviews with respondents, consisting of several members of Majelis Taklim Misbahus Sudur in Pidoli Dolok. The study is also supported by references from various literatures to strengthen the research findings. Data collection techniques include observation, interviews, and documentation. The researcher identified several findings and concludes that the Markhotom Al-Qur’an tradition at Majelis Taklim Misbahus Sudur serves as an expression of gratitude and a hope for blessings in all aspects of life, including health, inner peace, and sustenance. This tradition demonstrates that although it is practiced by a group of elderly women, it has a significant impact on shaping the spiritual and social character of the local community.